Recyclable photoresins for light-mediated additive manufacturing towards Loop 3D printing - Lopez de Pariza, Xabier; Varela, Oihane; Catt, Samantha; Long, Timothy E.; Blasco, Eva; Sardon, Haritz (Nature Communications, 2023)
Additive manufacturing (AM) of polymeric materials enables the manufacturing of complex structures for a wide range of applications. Among AM methods vat photopolymerization (VP) is desired owing to improved efficiency, excellent surface finish, and printing resolution at the micron-scale. Nevertheless, the major portion of resins available for VP are based on systems with limited or negligible recyclability. Here, we describe an approach that enables the printing of a resin that is amenable to re-printing with retained properties and appearance. To that end, we take advantage of the potential of polythiourethane chemistry, which not only permits the click reaction between polythiols and polyisocyanates in the presence of organic bases, allowing a fast-printing process but also chemical recycling, reshaping, and reparation of the printed structures, paving the way toward the development of truly sustainable recyclable photoprintable resins. We demonstrate that this closed-loop 3D printing process is feasible both at the macroscale and microscale via DLP or DLW, respectively.
Online veröffentlicht: 7. September 2023
Gesehen am 29.11.2023